Analysis of The Leadership Empowerment Principles of The Principal of SMPN 2 Piabung Anambas Islands District - Anggi Ariska; Amrozi Khamidi; Meini Sondang Sumbawati (Cetta: Jurnal Ilmu Pendidikan, 2023)
Empowering school principals' leadership toward teachers is an indicator of behavior in improving the quality of education. This is the school principal's responsibility to foster and mobilize teaching human resources to improve the professionalism of their performance, including at SMPN 2 Piabung. This research aims to analyze the implementation of empowering school principals in developing professional teachers at SMPN 2 Piabung. The method in this study uses mixed methods research. Qualitative methods complement the use of quantitative methods. Data was collected through a questionnaire and participant observation. Statistical data analysis in the form of min, frequency, and mean for data presentation. Questionnaire data were analyzed using Software SPSS version 25.0, while qualitative data were analyzed by explanation. The results of the study show: (1) empowerment in the form of encouraging teachers to make effective use of school infrastructure, delegating tasks proportionally (task division), forming coordinators for academic development and extracurricular activities, and supervising the running of school programs and requesting reports on program implementation very high rating; (2) empowerment in the form of involving teachers in planning school programs, inviting teachers to develop knowledge, skills, and experience through training programs, carrying out responsibilities transparently and reporting every decision to get maximum results, and giving rewards (praise, encouragement, and feedback to the teacher) is at the moderate rating level.